Albani Inconsistency in Assessing The Quality of Rawi Hadith in The Book Irwā' Al-Galīl - Muhammad Rafi'iy Rahim; Mohamad Syafri (Al-Bukhari : Jurnal Ilmu Hadis, 2022)
Many figures in the field of Hadith science, including contemporary hadith figures, who tries to do an in-depth study. One who is considered as a prominent hadith figure in this modern age is al-Albani. In several of his books, al-Albani applies several methods that are considered by some to be new methods. One of Al-Albani's phenomenal books, Irwā al-Galīl fī Manār al-Sabīl, has become a reference for scholars who studies him. This study focuses on Al-Albani's method in determining status of rawi in the book Irwā al-Galīl fī Manār al-Sabīl. Using the qualitative method, within the framework of the design of the critique of Al-Albani's work. This study examines 2,707 hadiths contained in the book. This study finds that Al-Albani in the book often shows an inconsistent attitude in determining the status of a hadith rawi. The form of this inconsistency is found in the changing attitudes of Al-Albani in determining the status of several narrators, including Al-Sa'q bin Hazn, 'Aqil bin Mudrik, Mujja'ah bin Al-Zubair, Harun bin Antarah, 'Amr bin Malik, and 'Amr bin Abd Al-Rahman. From the results of the research found, a general conclusion can be drawn, that Al-Albani at Irwā al-Galīl fī Manār al-Sabīl still shows an inconsistent attitude, especially in determining the status of a narrator.